Проект електронного словника музичної термінології - Кульчицький, І.; Осідач, Н. (Лексикографічний бюлетень, 2011)
The article deals with the project of creation of an electronic dictionary of musical terminology on the basis of the Dictionary of musical terminology of 1930-ties and the Musical dictionary by Z. Lysko. The reasons influencing the choice of the subject of research are stated, the history of dictionary compilation is described. The method of returning lexicographic works into the science is justified, namely that of dictionary reproduction in an electronic form. The structure of the abovementioned lexicographic works is researched with the aim of discovering aspects which need improvement while creating an electronic dictionary of musical terminology. The authors stress the possibility of using the given work for the compilation of a new dictionary of Ukrainian musical terminology as well as for the creation of electronic dictionaries of the similar type.